"Body Shots": Analyzing shooting styles in the NBA using body pose - Felsen, P.; Lucey, P. (MIT Sloan Sports Analytics Conference 2017, 2017)
In this work we develop a novel attribute-based representation of a basketball player`s body pose during his three point shot. The attributes are designed to capture the highlevel body movements of a player during the different phases of his shot, e.g., the jump and release. Analysis is performed on 1500 labeled three point shots. Normalized for game context, we use Pearson`s Chi-squared test to quantify differences in attribute distributions for made and missed shots, where we observe statistically significant differences in distributions of attributes describing the style of movement, e.g., walk, run, or hop, in various phases of the shot. Similarly, with mixed shot outcomes, across game contexts, we observe statistically significant differences in distributions of attributes describing the pass quality, direction of movement, and footwork. We also present a case study for Stephen Curry, where we observe that Curry moves much more than the average player in all phases of his shot and he takes a higher proportion of off-balance shots compared to the average player